Data-Based Evidence on the Causality Model of Social Stigma on Medication Compliance in Leprosy Patients in Bone District, Indonesia - Bs. Titi Haerana; Mariani; Rismawati Aulia Insani Sadarang; Emmi Bujawati; Yudi Adnan; Nurdiyanah Syarifuddin (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2025)
Leprosy is an infectious disease and can cause stigma from society. One thing that is important to do to reduce the stigma felt by leprosy sufferers is to obediently take medication. This study aims to determine the relationship between stigma and adherence to taking medication on covariate variables in leprosy patients in Bone Regency. This quantitative study uses an observational analytical approach and a cross-sectional study. The analysis used was multivariate analysis with a causality model. The number of samples in this study was 92 respondents, taken using simple random sampling. The results of this study show that stigma in leprosy patients in Bone Regency is significantly related (ORa = 1.022, 95% CI = 0.306-3.416) to adherence to taking medication, which means 1.022 times more likely to experience non-adherence in taking medication, controlling for gender and side effects of medication. There needs to be preventive efforts through early detection and health education related to leprosy given to patients, the patient's family, and the community, so that it can reduce the stigma experienced by patients and increase compliance with taking medication.